Online teaching as the new normal: Understanding translator trainers' self-efficacy beliefs - Di Wu; Lan Wei (JoSTrans: The Journal of Specialised Translation)
The coronavirus disease (COVID-19) has turned most translator trainers around the world into online trainers, whether they were ready or not. With translator trainers gaining considerable first-hand experience from their remote teaching activities during COVID-19, this study set out to understand translator trainers' self-efficacy beliefs (e.g. trainers' judgement about their own abilities) regarding online teaching in the Australasian context. A total of 49 Australian and New Zealand translator trainers contributed to this study by completing an online survey, from which data about their demographic information, online teaching related experiences, and self-efficacy beliefs about online teaching were collected. Analyses of the data showed that the trainers did not have many opportunities to teach online before COVID-19. Similarly, they lacked experiences in professional training and self-study regarding online teaching. The trainers were generally not very confident in their abilities to teach translation online. The analyses also found that the trainers' self-efficacy beliefs about online teaching were more strongly correlated with some of their experiences (e.g. professional training, self-study, student feedback and student gain) than with other experiences (e.g. pre-pandemic online teaching, university support, and collegial help).